Pemetaan Mutu Pendidikan Anak Usia Dini Muslimat Nahdlatul Ulama - Trihantoyo, Syunu; Nursalim, Mochamad; Roesminingsih, Erny (LPM IHDN Denpasar, 2020)
The purpose of study was to determine the mapping quality of early childhood education either child care, play groups, kindergartens or raudlatul athfal in the District of Mojokerto. This research is a type of descriptive research with a quantitative approach. The design of this study used a survey method at Muslimat Nahdlatul Ulama (NU) Mojokerto regency. Sampling in this study using 82 samples of saturated sample techniques. Data analysis in this study uses descriptive analysis with a quantitative approach. The results of data analysis, from 82 PAUD institutions, it is found that the mapping of the quality of Early Childhood Education (PAUD) Muslimat NU Mojokerto Regency is mostly in high quality as many as 74 PAUD institutions (90.24%), in the current position there are 7 PAUD institutions (8.54%), and less categories by 1 PAUD institution (1.22%).